2021
DOI: 10.1016/j.apsb.2020.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BMI-1-mediated epithelial–mesenchymal transition to inhibit colorectal cancer liver metastasis

Abstract: Liver is the most common metastatic site for colorectal cancer (CRC), there is no satisfied approach to treat CRC liver metastasis (CRCLM). Here, we investigated the role of a polycomb protein BMI-1 in CRCLM. Immunohistochemical analysis showed that BMI-1 expression in liver metastases was upregulated and associated with T4 stage, invasion depth and right-sided primary tumor. Knockdown BMI-1 in high metastatic HCT116 and LOVO cells repressed the migratory/invasive phenotype and reversed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“… 86 Interestingly, the short-chain fatty acid sodium butyrate (NaB) produced by bacterial fermentation of dietary fiber in the colon limits colorectal cancer liver metastasis by downregulating BMI1 expression by enhanced miR-200c expression. 87 These results provide potential therapeutic agents for HCC.…”
Section: Overview Of Hcc Therapy Targeting Bmi1mentioning
confidence: 84%
“… 86 Interestingly, the short-chain fatty acid sodium butyrate (NaB) produced by bacterial fermentation of dietary fiber in the colon limits colorectal cancer liver metastasis by downregulating BMI1 expression by enhanced miR-200c expression. 87 These results provide potential therapeutic agents for HCC.…”
Section: Overview Of Hcc Therapy Targeting Bmi1mentioning
confidence: 84%
“…In the liver microenvironment, HSC-derived CAFs are the main tumor-interacting population and play a vital role in cancer cell metastasis (Zhao et ). We previously reported that BMI-1 was abnormally high expressed in CRLM and inhibition of BMI-1 in CRC cells dramatically reduced LM in vivo (Xu et al 2021). The normal liver cells were BMI-1 negative, we observed that BMI-1 positive liver cells were common in CRLM samples from humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…BMI-1 regulates self-renewal of stem cell and participate in carcinogenesis of human cancers, including CRC(Jiang et al 2009;Tateishi et al 2006;Gil et al 2005). We have previously reported that BMI-1 was overexpressed in CRLM and contributes to the LM by regulating epithelial-mesenchymal transition (EMT) of CRC cells in vitro and in vivo(Xu et al 2021). Interestingly, we observed BMI-1 positive staining in liver cells both in human and mice liver specimens of CRLM.…”
mentioning
confidence: 99%
“…The latter acted as a transcriptional repressor and is a member of the polycomb group of proteins which modify chromatin structure (41). BMI-1 mediates EMT, liver metastasis and drug resistance (42,43).…”
Section: Up-regulated Circrnas Conferring Drug Resistancementioning
confidence: 99%